2022
DOI: 10.7150/ijbs.76140
|View full text |Cite
|
Sign up to set email alerts
|

HDAC5-mediated Smad7 silencing through MEF2A is critical for fibroblast activation and hypertrophic scar formation

Abstract: Transforming growth factor-β (TGF-β) signaling plays a key role in excessive fibrosis. As a class IIa family histone deacetylase (HDAC), HDAC5 shows a close relationship with TGF-β signaling and fibrosis. However, the effect and regulatory mechanism of HDAC5 in hypertrophic scar (HS) formation remain elusive. We show that HDAC5 was overexpressed in HS tissues and depletion of HDAC5 attenuated HS formation in vivo and inhibited fibroblast activation in vitro. HDAC5 knockdown (KD) significantly downregulated TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…21,30 MEF2A is critical for the transcription regulation of Smad7 expression. 20 MEF2A is a transcription factor that plays an important role in the regulation of muscle development and function. 31,32 However, its role in renal fibrosis has not been fully studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,30 MEF2A is critical for the transcription regulation of Smad7 expression. 20 MEF2A is a transcription factor that plays an important role in the regulation of muscle development and function. 31,32 However, its role in renal fibrosis has not been fully studied.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HDAC5 can repress the transcription of Smad7 by repressing the transcriptional activity of MEF2A. 20,21 To verify this, we first examined the impact of HDAC5 knockdown under TGF-β stimulation and found that MEF2A expression also decreased, while Smad7 expression was recovered. These results demonstrate that HDAC5 regulated both MEF2A and Smad7 (Figure 6A-C).…”
Section: Hdac5 Interacted With Mef2a To Repress Smad7 Transcriptional...mentioning
confidence: 92%
“…[39] Recently, Ya Gao et al reported that LMK235 signi cantly alleviated hypertrophic scar formation in vivo, and HDAC5 knockdown inhibited TGF-β1-induced Smad2/3 phosphorylation and broblast activation in vitro. [40] Therefore, we hypothesized that LMK235 could suppress TGF-β1-induced broblast-myo broblast transformation by inhibiting Smad2/3 pathway activation in cardiac broblasts. In our study, we con rmed that LMK235 attenuated TGF-β1-induced broblast-myo broblast transformation by inhibiting Smad2/3 pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC5 is a member of the class IIa family histone deacetylase family, and it has been discovered to be closely related to the fibrosis; it can activate fibroblasts and facilitated the formation of hypertrophic scar. [ 30 ] In lung fibrosis tissues of mouse, the significantly upregulated HDAC5 has been researched. [ 31 ] Thus, HDAC5 is identified to be key gene involved in regulating fibrosis.…”
Section: Discussionmentioning
confidence: 99%